Prohibition! A Constitutional Promise And The Reality A study on Indian Made Foreign Liquor Markets in Kerala - Hareesh N Ramanathan Prof. Dr Jagathy Raj V P (International Marketing Conference on Marketing & Society, 8-10 April, 2007, IIMK, 2007)
Kerala has become very materialistic. Rapid changes have taken place in the material culture, but there has been no change at all in the State's non-material culture. Kerala society is caught in a cultural lag. The alcohol consumption rate in the state has increased manifold and it is today one of the highest in the country. The per capita consumption of alcohol in the state stands at 8.3 litres, according to the Alcohol and Drug Information Centre (ADIC), India. Twenty per cent of the population consumes alcohol. The average age of first consumption of liquor came down below 13yrs.The review of literature had revealed that most of the studies related to alcohol markets are confined to the study of the influence of rate of alcohol consumption due to changes in price at various levels, pattern of drinking levels, consequence of drinking, gender differences in drinking habits. Many studies also attempted to analyse pattern of preference between different alcohol types, influence of age on trends in alcohol use and the like. The exponential growth in the per capita consumption of alcohol among the Kerala population had motivated the researcher to study the pattern of growth during various periods. So it has become a necessity to study the demand tr end for Indian Made Foreign Liquor (IMFL) in Kerala. A close look at the past sales data over period of time can reveal the underlining socio-political situations that had contributed to the extra ordinary increase in the liquor consumption habits of Keralite's. An attempt to extrapolate the given trend to the future can also help to forecast the inevitable danger (if any) threatening to disturb the socio-cultural fabric of the conservative Kerala polity. An attempt was also made to study the vested interested (if any) of the political and Government leadership in floating the proclaimed prohibition policy of the state mentioned in Article 47 of the directive principles of state policy of the Indian Constitution